REL Healthy School: Health Innovation Through Coordinated School Health Program in YWKA Elementary School - Irma Darmawati (Indonesian Journal of Community Development, 2021)
Schools as places for teaching and learning to take place are expected to become Health Promotion Schools. This can be maximally pursued by planning innovative health program activities in schools. The implementation of this community service activity provides solutions through health innovation in Trias UKS using Coordinated School Health Program. The method of activity is community empowerment, which is accomplished through a series of outreach, training, education, and coaching activities. Dokcil Students in SD YWKA improved their cognitive, attitude, and behavior as a result of the practice.